Research on the Application of BIM Technology in the Design of Green Buildings - Zhao, Hongxiu; Li, Xiaoling; Qi, Yongcheng (2021 International Conference on E-Commerce and E-Management (ICECEM), 2021)
With the increasingly serious environmental problems, the country pays more and more attention to the green and low-carbon development of the construction industry and vigorously promotes the development of green buildings. In recent years, the rise of BIM technology has gradually been promoted in the construction industry. This article describes the overview of BIM technology and the concept of green buildings, combined with the Daxing Airport case to illustrate that BIM technology plays a vital role in green buildings, and it is of great significance to promote the use of BIM in green buildings.